Properties of the pulsed plasma-liquid systems with acoustic waves focusing - Sidoruk, S.M.; Yukhymenko, V.V.; Chernyak, V.Ya.; Marchuk, V.E.; Gavrylyuk, E.Yu.; Martysh, E.V.; Fedorovich, O.A. (Вопросы атомной науки и техники, 2012)
The plasma-liquid system with cylindrical geometry and electric pulse discharge less than 10 microseconds duration was created. The influence of plasma treatment to water pH value was investigated. Dependences of the phenol destruction efficiency in its aqueous solution, as a model contaminant, from the solution concentration was obtained and got the best efficiency value: 20 eV per phenol molecule at its water solution with concentration 0.3 M. In obtained absorption spectra remnants of nitric and nitrous acids and other components was not observed, such components was observed after phenol aqueous solution destruction in similar DC plasma-liquid systems. Разработана плазменно-жидкостная система цилиндрической геометрии с электрическим импульсным разрядом длительностью не более 10 мкс. Исследовано влияние плазмохимической обработки воды на ее водородный показатель рН. Получены зависимости эффективности деструкции фенола в водном растворе, в качестве модельного загрязнителя, от концентрации раствора, и получен наилучший уровень эффективности: 20 эВ на молекулу фенола при концентрации раствора 0,3 М. На полученных спектрах поглощения отсутствуют остатки азотной и азотистой кислот, а также других соединений, которые наблюдаются при деструкции фенола в его водных растворах в подобных плазменно-жидкостных системах постоянного тока. Розроблено плазмово-рідинну систему циліндричної геометрії з електричним імпульсним розрядом тривалістю менш ніж 10 мкс. Досліджено вплив плазмохімічної обробки води на її водневий показник рН. Отримані залежності ефективності деструкції фенолу у водяному розчині, в якості модельного забруднювача, від концентрації розчину, та отримано найкращий рівень ефективності: 20 еВ на молекулу фенолу при концентрації розчину 0,3 М. На отриманих спектрах поглинання відсутні залишки азотної та азотистої кислот, а також інші сполуки, що спостерігаються при деструкції фенолу в його водяних розчинах в подібних плазмово- рідинних системах постійного струму.